Affective Engagement in Metaphorical versus Literal Communication Styles in Counseling. Issue 4 (20th April 2020) - Tay, Dennis
ABSTRACT: Metaphor theory bears many implications for counseling processes, but metaphor in extended counseling talk is seldom evaluated. This article reports an exploratory skin conductance and discourse analysis of metaphorical versus literal communication styles in facilitating affective engagement over time. After background interaction with the counselor-experimenter, role-playing clients ( N = 60) were asked either a metaphorical or literal stimulus question related to the topic of academic problems. This was followed by spontaneous elaboration of either stimulus. A mixed-effects model with random subject intercepts suggests that both styles are tied to increased affective engagement, but the increase was significantly more apparent in the metaphorical style. However, no significant differences were found immediately after stimulus. The results are corroborated by a post-experiment survey where the metaphorical style was rated significantly better for expressing emotions and experiences and introducing new frames of reference. A further exploratory analysis of discourse features uncovered key components of the metaphorical style and their specific implications for engagement. The study suggests that a metaphorical style is more affectively engaging but requires sustained follow-up and spontaneous metaphor elaboration skills. Limitations are critically discussed, given the infancy of the present approach.